2021
DOI: 10.1038/s41467-021-23956-6
|View full text |Cite
|
Sign up to set email alerts
|

4D polycarbonates via stereolithography as scaffolds for soft tissue repair

Abstract: Abstract3D printing has emerged as one of the most promising tools to overcome the processing and morphological limitations of traditional tissue engineering scaffold design. However, there is a need for improved minimally invasive, void-filling materials to provide mechanical support, biocompatibility, and surface erosion characteristics to ensure consistent tissue support during the healing process. Herein, soft, elastomeric aliphatic polycarbonate-based materials were designed to undergo photopolymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 62 publications
1
100
0
Order By: Relevance
“…19 However, there are only a few examples of biodegradable photopolymers that are suitable for SLA or DLP 3D printing of elastomers with tuneable mechanical properties. [20][21][22][23] In general, most of the biodegradable photopolymers designed for SLA or DLP (e.g., acrylated poly(lactide) (PLA) 24,25 or poly(ε-caprolactone) (PCL) 26 ) have low molecular weights (MW, typically 600-3000 g mol −1 ) in order to keep the viscosity of the resin low, resulting in brittle 3D printed products (tensile strain <50%). Grijpma, Seppälä et al showed that at higher MW, the photopolymers become solid and almost unprintable at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 However, there are only a few examples of biodegradable photopolymers that are suitable for SLA or DLP 3D printing of elastomers with tuneable mechanical properties. [20][21][22][23] In general, most of the biodegradable photopolymers designed for SLA or DLP (e.g., acrylated poly(lactide) (PLA) 24,25 or poly(ε-caprolactone) (PCL) 26 ) have low molecular weights (MW, typically 600-3000 g mol −1 ) in order to keep the viscosity of the resin low, resulting in brittle 3D printed products (tensile strain <50%). Grijpma, Seppälä et al showed that at higher MW, the photopolymers become solid and almost unprintable at room temperature.…”
mentioning
confidence: 99%
“…19 However, there are only a few examples of biodegradable photopolymers that are suitable for SLA or DLP 3D printing of elastomers with tuneable mechanical properties. 20–23…”
mentioning
confidence: 99%
“…For example, the photopolymerizable groups can be introduced by the side-group functionalization of ROP monomers, allowing the control of the photocrosslinkable sites in the resulting polymers. [82,83] More polymeric topologies (i.e., bottlebrush and hyperbranched polymers) that are rarely reported for photopolymerization 3D printing but exhibit potentially low intrinsic viscosity could also be investigated. [84,85] Random and block copolymerizations can provide various opportunities for further tuning the mechanical properties of the crosslinked networks.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they are smart materials with the shape memory characteristics which do not give impact or without deforming the surrounding environment. As a DMA uniaxial tensioncompressed to 80% strain and allowed to recover at 37 C in PBS [27] result, they are more efficient and smarter than typical materials.…”
Section: Fundamental Of Shape Memorymentioning
confidence: 99%